2012
DOI: 10.1186/1749-8090-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and pre-inflammatory stress in wedge resection of pulmonary parenchyma using the radiofrequency ablation technique in a swine model

Abstract: BackgroundRadiofrequency ablation (RFA) is a thermal energy delivery system used for coagulative cellular destruction of small tumors through percutaneous or intraoperative application of its needle electrode to the target area, and for assisting partial resection of liver and kidney. We tried to evaluate the regional oxidative and pre-inflammatory stress of RFA-assisted wedge lung resection, by measuring the MDA and tumor Necrosis Factor Alpha (TNF-α) concentration in the resected lung tissue of a swine model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In an animal study, a statistically significant increase in regional oxidative stress was observed only when the pulmonary resection by radiofrequency ablation technique was used [11]. In the present study, a benign or malignant indication of thoracotomy did not influence the amount of inflammation.…”
Section: Discussionmentioning
confidence: 49%
“…In an animal study, a statistically significant increase in regional oxidative stress was observed only when the pulmonary resection by radiofrequency ablation technique was used [11]. In the present study, a benign or malignant indication of thoracotomy did not influence the amount of inflammation.…”
Section: Discussionmentioning
confidence: 49%
“…Splenosis is most prevalent in the abdomen and, much less commonly, in the thorax [6]; here, we report a case of disseminated asymptomatic splenosis localized to the left pleural cavity and upper right and left quadrants in a 38-year-old male with a remote history of motor vehicle trauma.…”
Section: Introductionmentioning
confidence: 83%
“…The mean time between the injury responsible for splenosis and the actual diagnosis is about 2 decades [5]. Nevertheless, there are reports of splenosis presenting as persistent chest pain [6], [7], hemoptysis [8], and bowel obstruction [9]. Although diagnosis via biopsy is the gold standard, imaging informed by a relevant patient history including splenectomy or prior trauma to the spleen, is still acceptable [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation is a mature mechanism of cell damage in plants and animals, and it is used as an indicator of oxidative stress in cells and tissues. [28] Several experiments have shown that serum examination of MDA and SOD can refl ect the degree of oxidative damage to tissues. [29,30] MPO is an important enzyme released by neutrophils, and promotes the formation of hypochlorous acid, a powerful oxidant associated with bactericidal effects and tissue destruction through induction of necrosis and apoptosis.…”
Section: Discussionmentioning
confidence: 99%